Forensic Pathological Considerations of a Unique Case of "Complicated Suicide"*, †. Issue 6 (31st July 2020) - Gentile, Guendalina; Bianchi, Marta; Boracchi, Michele; Goj, Carlo; Tambuzzi, Stefano; Zoja, Riccardo
Abstract: In the forensic literature, peculiar and uncommon cases of suicides defined as "complicated" are reported. In these circumstances, the suicide method chosen by the victim fails, and death occurs due to a subsequent unforeseen accidental event defined as secondary trauma. Through retrospective examination of 25, 512 autopsies in 27 years (1993–2019) at the Bureau of Legal Medicine of Milan, a unique case of complicated suicide was identified from a total of 4497 suicides. It concerns an elderly man who, after killing his wife by inflicting incised wounds to her neck, tried to hang himself by tying a rope to a heater and jumping from the window located over the heater itself. However, the rope suddenly snapped and the man fells to the ground causing fatal traumatic injuries. Death occurred because of an accidental event caused by the failure of the hanging mechanism. Therefore, a peculiar yet characteristic case of complicated suicide is described.